The effect of selective serotonin reuptake inhibitors on the hemostasis system in patients with craniocerebral trauma - Bedlinskyi, Volodymyr (Psychosomatic Medicine and General Practice, 2018)
Background. Due to the increased prevalence of depressive disorders, the demand for antidepressants also increases. One of the most popular pharmacological groups is selective serotonin reuptake inhibitors. Although, their admission not always can be safe in some categories of patients, among formers can be patients with head injuries. Aim. Main mechanisms of SSRI negative influence on hemostatic system analysis in patients with depression and TBI. Finding ways to solve this problem. Methods. The bibliographic databases such as Pubmed, Web of Science and Google Scholar for keywords: organic depression, disorder, depression, SSRI, TBI, hemostasis changes were analyzed. Results. The general information about serotonin, its role in neurotransmission and the influence on the hemostatic system were studied. There’re shown the main mechanisms of SSRI influence on intra-thrombocytes serotonin. The main risk factors for SSRI admission in patients with depression with TBI were studied. We also have studied the SSRI admission in these painful patients. Some ways of solving the problem of treatment of patients with depression on the background of TBI are proposed.